2020
DOI: 10.1101/2020.02.15.950816
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Test of Memory: The Fish, The Mouse, The Fly And The Human

Abstract: Simple mazes have provided numerous tasks for assessing working memory. The discrete nature of choices in the T-maze has provided a robust protocol with sensitivity to cognitive deficits, whilst the continuous Y-maze reduces manual handling and pre-trial training. We have combined these attributes to develop a new behavioural task for assessing working memory, the Free-movement pattern (FMP) Y-maze. Using sequentially recorded left and right turns we demonstrate that zebrafish and mice use a single dominant st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 38 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…Critically, the FMP Y‐maze is conceptually more comparable to a series of discrete choices as would be the case in a series of trials in a T‐maze, or in a two‐choice guessing task (Cleal & Parker, 2018; Fontana, Cleal, Clay, & Parker, 2019; Fontana, Cleal, & Parker, 2019). We have demonstrated that alternations in turn‐direction are reduced following administration of memory‐impairing drugs (e.g., MK801 and scopolamine), suggesting that alternations are indicative of working memory (Cleal et al., 2020). Fish ( n = 48) were placed, individually, in a Y‐shaped maze (6.5 cm length × 1 cm width; three identical arms at a 120° angle from each other) with white opaque walls (Figure 1b) and recorded for 15 min.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…Critically, the FMP Y‐maze is conceptually more comparable to a series of discrete choices as would be the case in a series of trials in a T‐maze, or in a two‐choice guessing task (Cleal & Parker, 2018; Fontana, Cleal, Clay, & Parker, 2019; Fontana, Cleal, & Parker, 2019). We have demonstrated that alternations in turn‐direction are reduced following administration of memory‐impairing drugs (e.g., MK801 and scopolamine), suggesting that alternations are indicative of working memory (Cleal et al., 2020). Fish ( n = 48) were placed, individually, in a Y‐shaped maze (6.5 cm length × 1 cm width; three identical arms at a 120° angle from each other) with white opaque walls (Figure 1b) and recorded for 15 min.…”
Section: Methodsmentioning
confidence: 97%
“…The use of the overlapping tetragrams (four choices) was used as it gives a higher chance of identifying random search patterns than using sequences of two or three choices (Frith & Done 1983). Therefore, FMP Y‐maze behavior was analyzed through 16 possible four‐trial outcomes (tetragrams) for each fish as a proportion of the total number of turns to examine, in detail, their behavior patterns (Cleal et al., 2020; Cleal & Parker, 2018; Gross, Engel, Richter, Garner, & Wurbel, 2011). If behavior was fully random, it would be predicted that each choice would be equally likely (i.e., the predicted frequencies would be equal for each tetragram).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation